PERILAKU MEMAAFKAN DI KALANGAN REMAJA BROKEN HOME - Putri, Sri Wahyu (EMPATHY Jurnal Fakultas Psikologi, 2014)
ABSTRACTForgiving is an act of manifestation and valuable personal assets to resolve conflicts or problems among adolescences. Develop a forgiving behavior can bring many benefits for teens, providing both mental and physical health, improved relationships with others, pay attention to the well-being of others and is a form of moral action. The objective of study was to examine the psychological aspects of forgiving behavior in adolescents broken home and the factors that influence forgiving behavior in broken home adolescences. This study used a qualitative approach with case study method. Data was collected by using interviews and observations technique on sampling criteria that have adolescents aged 17-22 years with a broken home. The results showed the psychological aspects that occur on the subject is, the cognitive subject to forgive without any sense of revenge in our hearts, forgive affectively with compassion but not with forced. The factors that influence forgiving behavior in adolescence broken home is building a good relationship with others after conflicted.Keywords: behavioral forgive, broken home.